A predictive control based on decentralized fuzzy inference for a pH neutralization process. (February 2022) - Wu, Hui; Yan, Fei; Wang, Guangjun; Lv, Cai
Abstract: In this paper a predictive control method based on decentralized fuzzy inference (DFIPC) is proposed to deal with the problems of strong nonlinearity, large hysteresis and uncertainty in pH neutralization process. Firstly, the localized linearization of the non-linear object model is performed, and the future output of the control object is predicted based on the step response models of the linearized objects. Secondly, a decentralized fuzzy inference structure is designed, which is based on the deviation information between the expected value and the predicted value in a future time, and the control output of the system is generated by the weighted synthesis of the decentralized inference results. Finally, to verify the effectiveness, the proposed scheme is applied to the pH neutralization process. The results indicate that the proposed scheme not only possesses good tracking and anti-disturbance ability, but also shows better robustness and performance than the conventional model predictive control. Highlights: A predictive control method based on decentralized fuzzy inference (DFIPC) is proposed. The DFIPC performs better than DMC in pH neutralization process. The DFIPC shows good tracking and anti-interference ability and better robustness.